Damage Detection in Flexible Plate Using Lamb Waves - Gonsalez, Camila Gianini [UNESP]; Franco, Vitor Ramos [UNESP]; Bueno, Douglas Domingues [UNESP]; Marqui, Clayton Rodrigo [UNESP]; Cavalini Junior, Aldemir A. [UNESP]; Lopes Junior, Vicente [UNESP] (Messe Bremen-hvg Hanseatische Veranstaltungs-gmbh, 2008)
This paper presents an experimental technique for structural health monitoring (SHM) based on Lamb waves approach in an aluminum plate using piezoelectric material as actuators and sensors. Lamb waves are a form of elastic perturbation that remains guided between two parallel free surfaces, such as the upper and lower surfaces of a plate, beam or shelf. Lamb waves are formed when the actuator excites the surface of the structure with a pulse after receiving a signal. Two PZTs were placed in the plate surface and one of them was used to send a predefined wave through the structure. Thus, the other PZT (adjacent) becomes the sensor. Using this methodology, this paper presents one case of damage detection considering the aluminum plate in the free-free-free-free boundary condition. The damage was simulated by adding additional mass on the plate. It is proposed two damage detection indexes obtained from the experimental signal, involving the Fast Fourier Transform (FFT) and the power spectral density (PSD) that were computed using the output signal. The results show the viability of the presented methodology to damage detection in smart structures